Nitric oxide and auxin regulate root meristem during gravitropism in Arabidopsis thaliana - Vazquez, Maria Magdalena (2019)
The mevalonate pathway catalyzes the de novo synthesis of cholesterol, but also provides isoprenoids that may be used for protein modification through a complex process known as prenylation. Some proteins involved in oncogenic processes, such as Ras and Rho GTPases are among the targets of this modification. Pioneering studies with statins have suggested that mevalonate pathway alteration cooperates with tumor aggressiveness. More recently, other evidence has confirmed that alteration of this pathway may promote aggressive phenotypes and pointed out at enhanced protein prenylation as a possible mechanism underlying this effect. ICMT plays a central role in this posttranslational modification process by catalyzing the last step, carboxymethylation of the prenylated C-terminus in target proteins. We have recently unveiled a link between post-prenylation processing and the p53 pathway by showing that ICMT expression is repressed by wt p53, but enhanced by cancer-associated p53 point mutants. Moreover, our analysis of Breast and Lung cancer databases showed a negative correlation between ICMT expression and wt p53 status. Moreover, we found a significantly decreased metastasis-free survival frequency in patients with high ICMT expression. Basing on these results, we wondered if alteration of ICMT levels enhances metastasis development. To answer this question, we studied the effect of ICMT overexpression on metastasis in vivo, using Triple Negative Breast Cancer cells in an immunocompetent mouse model. We extended our previous analysis on breast cancer patients and we found that p53 status affects the impact of ICMT overexpression on clinical outcomes. Besides, our studies on the regulation of ICMT expression showed that other p53 family members affect its transcription. Our results suggest that ICMT levels are affected by alterations in the functional equilibrium between different members of this family during tumor progression. To explore the potential of pharmacological manipulation of ICMT function, we analyzed the impact of the ICMT inhibitor Cysmethynil to affect tumor-associated phenotypes. We found that ICMT inhibition affects clonogenic potential, as well as phenotypes associated with metastatic cells, such as migration and invasion in vitro. In an effort to develop novel ICMT inhibitors and inspired on Salirasib (S-trans-trans-farnesylthiosalicylic acid) we synthesized novel thiosalicylic acid derivatives. As a preliminary characterization, we analyzed the antiproliferative activity of our compounds in vitro on MDA-MB-231 cells. Our results suggest that ICMT overexpression affects tumor progression and that molecules interfering with the function of prenylated proteins are potentially useful in therapeutic strategies.